2021
DOI: 10.1097/scs.0000000000007754
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Divine Proportion for the Construction of the Visualized Treatment Objective in Craniofacial Surgery

Abstract: Aesthetics and function of maxillofacial district are closely related and could interfere with patient psychological conditions. The aim of this paper is to describe and to analyze the procedures necessary for a proper surgical visualized treatment objective (VTO) realization through the use of the tracing on lateral head film, applying the divine proportion (or golden ratio) in certain steps. The method described is easy to realize, cheap and help both orthodontist and maxillo-facial surgeon to communicate ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 44 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…The purposes of VSP are to determine the optimal position of the osteotomy line, which can improve facial esthetics, reveal bony interference between proximal and distal mandible segments, and put the least pressure on condyles. Presurgical visualization of surgical treatment objective guides clinicians to find optimal balance between functionality and esthetic maxillomandibular proportions 18. Then, precise transfer of the surgical plan to the actual operation is possible with the help of the customized CAD/CAM-printed surgical guides, wafers, and osteosynthesis plates.…”
Section: Discussionmentioning
confidence: 99%
“…The purposes of VSP are to determine the optimal position of the osteotomy line, which can improve facial esthetics, reveal bony interference between proximal and distal mandible segments, and put the least pressure on condyles. Presurgical visualization of surgical treatment objective guides clinicians to find optimal balance between functionality and esthetic maxillomandibular proportions 18. Then, precise transfer of the surgical plan to the actual operation is possible with the help of the customized CAD/CAM-printed surgical guides, wafers, and osteosynthesis plates.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive skeletal, dentaland esthetics cephalometric evaluation is the key point to the success of the result [ 18 ]. During the 3-year treatment period, the statistical analysis of X-ray lateral cephalometric film data before and after the treatment of the children, the study showed that SNA (+ 1.29°), ANB (+ 1.98°), and NA-PA(+ 1.93°) in sagittal bone surface indexes of the upper and lower jawbones increased, while SNB (-0.71°) decreased, the sagittal anomalies of the jawbones were improved, and there were significant differences before and after treatment ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the affected side also negatively conditions the development of musculature, resulting in the atrophy of the masseter and the internal pterygoid muscles, which are less stretchable and more fibrotic. Therefore, in the absence of a correct restoration of symmetry and function, the subsequent surgery would bear a substantially higher risk of failure owing to the tendency of muscles to relapse and midface asymmetry which would likely require orthognathic surgery as well, not to mention the psychosocial and emotional implications that the missed restoration of facial harmony and function would have on the child patient [34].…”
Section: Discussionmentioning
confidence: 99%